Working Parents, Financial Insecurity, and Child-Care: Mental Health in the Time of COVID-19 - Massimiliano Tani; Zhiming Cheng; Silvia Mendolia; Alfredo R. Paloyo; David Savage (Institute of Labor Economics (IZA), 2020)
The COVID-19 pandemic and the policy measures to control its spread – lockdowns, physical distancing, and social isolation – has coincided with the deterioration of people's mental well-being. We use data from the UK Household Longitudinal Study (UKHLS) to document how this phenomenon is related to the situation of working parents who now have to manage competing time demands across the two life domains of work and home. We show that the worsening of mental health in the United Kingdom is worse for working parents, and that it is especially related to the increased financial insecurity and the time spent on childcare and home schooling. We find that this burden is not shared equally between men and women, and between richer and poorer households. In crafting public policy responses to the pandemic, better outcomes can be achieved if policymakers are cognizant of these inequalities.
Keywords: I14; J16; 330; COVID-19; working parents; United Kingdom; childcare; mental health; financial insecurity